Kimia Medisinal dan Perjalanan Obat: Dari Desain Molekul Hingga Monitoring Klinis - Syakila Syalsa Reiza Putri; Saeful Amin (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study explores the role of medicinal chemistry in the entire drug development process, from molecular design to post-marketing monitoring. Using a literature study method with a descriptive qualitative approach, data were collected from various scientific journals published between 2020 and 2025 that are relevant to drug development and the application of medicinal chemistry. The findings indicate that medicinal chemistry plays a crucial role in designing, modifying, and optimizing the structure of bioactive compounds through approaches such as structure–activity relationship (SAR) analysis, in silico modeling, and modern biotechnology. These approaches enable the discovery of new compounds that are more selective, effective, and safe. Examples include natural compounds such as betel leaf (Piper betle), green tea, berberine, and curcumin derivatives, which show potential as anticancer, antiviral, and antimalarial drug candidates. In addition, biotechnology-based therapies such as trastuzumab highlight the success of medicinal chemistry in the development of targeted therapies. However, the translation process from laboratory research to clinical application still faces several challenges, including high research costs, preclinical data reproducibility issues, limited infrastructure, and strict regulatory frameworks. Therefore, multidisciplinary collaboration, methodological innovation, and supportive policy development are required to strengthen the translation of research outcomes. Overall, medicinal chemistry plays a strategic role in accelerating the discovery of new drugs that are safe, effective, and globally competitive. The findings also show that integrating traditional approaches with modern computational methods and multidisciplinary collaboration can further accelerate new drug discovery.